Dislocation mobility and critical stresses at finite temperatures in molecular crystal cyclotetramethylene tetranitramine (β-HMX). (6th November 2018) - Khan, Mohammad; Pal, Anirban; Picu, Catalin R
Abstract: Cyclotetramethylene tetranitramine (HMX) is an energetic material commonly found in plastic bonded explosives. Its crystallographic sensitivity to initiation and detonation has been linked to plastic slip in the various crystalline planes; shock directions which cannot accommodate substantial crystalline slip are expected to be more sensitive. In this work, we carry out constant stress-constant temperature molecular dynamics simulations of the motion of dislocations and characterize their behavior in the two most probable slip planes, (101) and (011), of this crystal. We evaluate critical thresholds for activating steady-state dislocation motion and the associated dislocation mobilities at various temperatures below 400 K. This information can be used to develop and calibrate larger scale models of plastic deformation in this material.